#TITLE_ALTERNATIVE# - Ayuningtyas (NIM 190 04 029) , Prameswari
Abstract: Capital market is a growing business sector in Indonesia, and year 2006-2007 might have become spectacular period of JSX because market has understanding performance. This research attempts to answer the question, does capital market in Indonesia is efficient and the current market price reflects all available information The research also expects to describe the capital market pattern and behavior in Indonesia. This research is an implementing only of the Weak Form of Efficient Market Hypothesis using empiric composite index (IHSG) and LQ45 from Jakarta Stock Exchange period 2005-2006. Autocorrelation analysis is used to measure the strength and direction of data correlation and regression analysis is used to show relationship the equation between variable. The outcome shows that capital market is not efficient and the current market price did not reflect all available information, then investor can predict the future price. The result is parallel with Manurung paper (1997) that also tests Weak Form of Efficient Market Hypothesis of the Jakarta Stock Exchange. Additionally, this research shows that both IHSG and LQ45 index illustrate unique behaviour and pattern from Indonesian market.